Structural design of culvert joints - Moore, Ian D. (National Cooperative Highway Research Program, Transportation Research Board of the National Academies, 2012)
This document explores the effect of longitudinal bending on joints in rigid (reinforced concrete) and flexible (corrugated steel and thermoplastic) culverts.
"Contractor's final report for NCHRP Project 15-38, submitted April 2012."
Keywords: Culverts -- Design and construction.; Drainage.; Joints (Engineering); elektronické knihy; electronic books